Modified robust time delay estimation algorithm based on cyclostationarity in impulsive noise - Yang LIU; Tian-shuang QIU; Jing-chun LI (Tongxin xuebao)
The problem of time delay estimation (TDE) for cyclostationary signals in the presence of α-stable distribution impulsive noise and interfering signals was addressed.Since the conventional algorithms based on the second-order cy-clic spectral correlation function degenerated severely in impulsive noise environment,a novel robust algorithm based on the fractional lower-order spectrum was proposed.Compared with conventional spectra analysis methods,this novel method could suppress Gaussian noise,non-Gaussian impulsive noise and interfering signals more effectively.Simulation results demonstrate the effectiveness and robustness of the novel algorithm.